(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses agrammatism in the speech of bilingual children, psycholinguistic foundations and features of agrammatism. Agrammatism is a violation of grammatical norms in speech activity. In this paper, we proceed from the statement that the causes of such disorders are not physiological or psychological disorders in development, but the presence of children in a bilingual environment and speech interference. The article examines the interaction of unrelated languages – Russian with Turkic languages, namely, Uzbek. Examples from the live speech of children who were monitored are given. All of them are at the 3rd stage of ontogenesis – preschool. This stage is characterized by the fact that children develop phonemic hearing, vocabulary grows and lexical meanings of words are enriched, complex constructions are mastered when composing sentences, etc. Children who have no idea about grammatical categories and rules often have speech errors associated with different levels of language: word formation (word-making), morphology, syntax, etc. As a result, it was revealed that agrammatism in the speech of bilingual children is more common in the early stages of speech development and is an inevitable step in mastering a foreign language. The use of agrammatism is associated equally with speech interference, and with familiarization with new, complex concepts and constructions in the language being studied.